Analysis on Volatile Components of Whole Milk Powder under Different Rehydration Processes by Comprehensive Two-Dimensional Gas Chromatography-Mass Spectrometry - Yuan LIU; Chunping JIN; Zhilei JIA; Yongmeng FU; Baosen AN; Feihong XU; Ruidong FU; Ping WANG; Qiang ZOU; Qiming LI (Shipin gongye ke-ji, 2023)
In order to optimize the rehydration process of whole milk powder and explore the effect of low temperature rehydration on the flavor of reconstituted milk, headspace solid phase microextraction (HS-SPME) combined with comprehensive two-dimensional gas chromatography-mass spectrometry (GC-GC-MS) was used in this study. The percentage of main volatile compounds in the reconstituted milk was investigated under the process conditions of single-stage rehydration (55 ℃ for 30 min) and two-stage rehydration (4 ℃ for 4, 8 and 12 h after rehydration 55 ℃ for 30 min). The ROAV method and principal component analysis were used to analyze the flavor contribution of volatile substances to the reconstituted milk. The results showed that a total of 68 kinds of volatile substances divided into 9 types, such as alcohol, ether and furan were identified in the 4 groups of reconstituted milk samples. Among these substances, dodecanol, n-hexanal, n-octaldehyde, nonanal, trans-2-octenal, decanal, and trans-2-nonanal were the common characteristic flavor substances in the four groups of reconstituted milk, the contribute of aldehydes to the reconstituted milk was more than that of other volatile compounds. The single-stage hydration reconstituted milk was well differentiated from the two-stage hydration reconstituted milk by principal component analysis. The rehydration process at 4 ℃ was beneficial to reduce the smell caused by 1-octene-3-alcohol, dodecanol and trans-2-decenoaldehyde. The rehydration process at 4 ℃ for 8 h was the most beneficial to improve the beneficial flavor of the reconstituted milk, which was the best rehydration process. The results could provide a reference for the industrial production of reconstituted milk.